Identification Of Cadmium (Cd) Content In The Catch Cumi (Loligo Sp) In Langgula Village, Sub-District Batudaa Beach, Gorontalo Regency - Apriliany Putri Rauf; Herlina Jusuf; Tri Septian Maksum (Universitas Muhammadiyah Palu, 2026)
Animal food that is suitable for consumption must be safe, nutritious, contamination-free, and halal. Squid (Loligo sp) is a carnivorous animal that is widely found in Langgula Village, Batudaa Pantai District, Gorontalo Regency and is a leading commodity with an average catch of 450 kg/month or 15 kg/day. One of the threats to the quality of squid is the pollution of the heavy metal cadmium (Cd) which is toxic, cannot be degraded naturally, and easily accumulates in marine organisms, thus potentially endangering human health and ecosystems through the processes of bioconcentration, bioaccumulation, and biomagnification. This study aims to identify the heavy metal content of cadmium (Cd) accumulated in squid (Loligo sp) in Langgula Village, Batudaa Pantai District, Gorontalo Regency. The type of research used is quantitative research using a descriptive approach method aimed at describing the content of Cd in squid. Samples were obtained from four collection points. The analysis of the content of Cd used the Atomic Absorption Spectrophotometry (AAS) method. The results showed that the heavy metal content of cadmium (Cd) contained in squid (Loligo sp) at point 1 was 0.182 mg/kg, at point 2 as much as 0.114 mg/kg, at point 3 as much as 0.278 mg/kg, and at point 4 as much as 0.385 mg/kg. These results show that the heavy metal content of cadmium (Cd) in squid (Loligo sp) exceeds the quality standard according to the Food and Drug Control Agency of the Republic of Indonesia (BPOM) Number 23 of 2017, which is 0.10 mg/kg, so it is not safe for consumption. The results of the research are expected to be considered for local governments and communities in managing fishery resources, preventing pollution, and educating the public about the dangers of heavy metals to health and can use natural ingredients to reduce the Cd content in squid before processing.